The new book of world rankings - George Thomas Kurian (Facts On File, 1991)
The book presents fascinating comparisons of nations large and small, weak and powerful, developed and underdeveloped - more than 200 nation-states or territories. The 230 subjects covered in this book range from such vital issues as population and the environment to intriguing comparisons of national drinking habits and library usage. The book also presents country profiles, describing each country briefly in light of the rankings